2019
DOI: 10.15689/ap.2019.1804.18859.02
|View full text |Cite
|
Sign up to set email alerts
|

Avanços na Psicologia Positiva: Bem-Estar, Engajamento e Redesenho no Trabalho

Abstract: Baseados na perspectiva da complexidade do comportamento humano, avanços científicos têm sido obtidos por pesquisadores da Psicologia Positiva ao identificar fatores de saúde e de proteção das pessoas em concomitância com os de risco de dano ou agravo á saúde. Esse artigo teórico visa demonstrar o impacto desses achados para a Psicologia Organizacional e do Trabalho, com base em três conceitos centrais. São apresentados no artigo os modelos teóricos que fundamentam as evidências e os principais achados nos est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 34 publications
(54 reference statements)
1
5
0
4
Order By: Relevance
“…Interventions in the field of psychiatry and PP also deserve attention, especially since there are already studies carried out with online interventions, which are particularly necessary during social distancing. 54 A survey that evaluated the effects of an individual online PP intervention focused on positive emotions, self-efficacy, and engagement at work. A total of 86 participants in the intervention group completed the study, which showed a significant impact on positive emotions and self-efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Interventions in the field of psychiatry and PP also deserve attention, especially since there are already studies carried out with online interventions, which are particularly necessary during social distancing. 54 A survey that evaluated the effects of an individual online PP intervention focused on positive emotions, self-efficacy, and engagement at work. A total of 86 participants in the intervention group completed the study, which showed a significant impact on positive emotions and self-efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Hope serves as a personal resource in the workplace, where an individual is constantly subjected to emotional, physical, and psychological demands. It has the potential to promote a future-oriented motivational state that can help those individuals plan ways to achieve their goals and develop practical actions to succeed (Bakker & Demerouti, 2017 ; Leiter, 2021 ; Vazquez et al, 2019 ), and experience higher levels of work engagement (Hofkamp et al, 2020 ; Sarfraz et al, 2019 ). Also, there is evidence that hope acts as a protective factor against burnout at work (Passmore et al, 2020 ; Yotsidi et al, 2018 ).…”
Section: Dispositional Hope and Mental Healthmentioning
confidence: 99%
“…In the Job Demand-Resources (JD-R) theoretical model, engagement at work is defined as a positive mental state in which energy is mobilized in productive work activities with intense pleasure and achievement, identifying in this phenomenon the levels of vigor, dedication and absorption and its performance as an outcome indicative of occupational health (Schaufeli et al, 2013;Vazquez & Schaufeli, 2020).…”
Section: Positive Psychology Interventions In Healthmentioning
confidence: 99%